The Political economy of growth and impoverishment in the Marcos era - Boyce, James K. (Manila, Philippines : Ateneo De Manila University Press, 1993)
This volume forms part of a series on economic choices before the developing countries. the experience of economic development over more than four decades is varied and rich, and it is possible to learn much from it, both analytically and in terms of economic policy.
1. The setting -- 2. Growth and distribution: an overview -- 3. The green revolution -- 4. What price rice? -- 5. The new rice technology and rural inequality -- 6. farming for the world market -- 7. Export agriculture: whose advantage? -- 8. Forestry: a squandered inheritance -- 9. Foreign borrowing -- 10. Capital fight -- 11. Debt for development.
Includes bibliographical references and index.
Keywords: ECONOMIC -- HISTORY